Dental Care during the COVID-19 Pandemic - Roman-Torres, Caio Vinicius G.; de Melo Quintela, Marcelo (Coronaviruses, 2021)
Background: The rampant spread of SARS-CoV-2 worldwide increases the likelihood that dental health care professionals will treat this subset of the patient population. Due to the characteristics of the profession and the virus, two situations deserve attention: the disinfection of surfaces that can be contaminated during dental treatment and the presence of the virus in the oral cavity and the countless possibilities of microbial interaction with microorganisms in the oral cavity. Objective: The objective of this review was to point out the current stage of the discussion on dental biosafety involving professionals, the work team and patients. Methods: The following databases were consulted: MEDLINE (National Library of Medicine, USA - NLM), Lilacs, Scielo, Embase, Web of Science and Google Academic with the keywords COVID-19 and dental practice, dentistry, oral conditions, mouthrinses. Results: Disinfection of surfaces has always been paramount and the protocol to prevent the spread of SARS-CoV-2 seems to be established. SARS-CoV-2 is vulnerable to oxidation, it is recommended to use a mouth rinse containing oxidizing agents. Conclusion: Dentists are among the professionals who are most at risk of COVID-19 infection, and they must have extra attention during this period, biosafety measures must be reinforced and patients must be motivated to maintain a strict oral hygiene routine so that there is no accumulation of biofilm and this may somehow interfere with their systemic condition.
Keywords: pandemic